Do Intangible Assets, Income Tax, and Debt Agreement Have an Impact on Transfer Pricing Strategy in Multinational Companies? - Kumala, Reza; Raffi Faruqi Ruslan, Muhamad; Murtanto, Murtanto (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Background: Intangible assets afford firms a degree of flexibility in establishing values for tax efficiency, yet they are not without inherent risks, as they are susceptible to manipulation. Prior research has yielded inconclusive results, creating ambiguity regarding the fundamental factors influencing transfer pricing decisions. This study is therefore of great importance, as it aims to provide clarity, reduce the risk of manipulation, and support fair regulations to promote good corporate governance. Objectives: This study employs a comprehensive approach to examine the influence of intangible assets, income tax, and debt covenants on transfer pricing practices within corporate entities. Method: The research employs quantitative methods and focuses on all companies listed on the LQ45 index of the Indonesia Stock Exchange. The data utilized in the study were obtained from secondary sources, and logistic regression was selected as the analytical technique. Results: The findings indicate that intangible assets and income tax have a notable impact on transfer pricing. However, it is important to acknowledge that the results in this domain remain inconclusive. In contrast, debt covenants were found to have no significant effect.